Statistical Analyses of Stock Level and Order Quantity for the KANBAN System - FUJITA, Seiichi; KOTANI, Shigenori; TAMURA, Takayoshi (Transactions of the Japan Society of Mechanical Engineers Series C, 1990)
KANBAN is known as a practical tool to control the inventory of materials and the timing of production. This paper presents a probabilistic model for the KANBAN system, considering such parameters as shipping frequency per day, traveling lead-time of KANBAN, consumption variation of materials and overtime. Some statistical analyses concerning inventory levels and order quantities of materials are carried out.